Permainan Tradisional Congklak terhadap Pengembangan Kecerdasan Logis Matematis Anak (Journal of Telenursing (JOTING), 2024)
This research aims to determine the influence of traditional games on the development of children's mathematical logical intelligence in preschool Kartika and Dta Al-Bilal, Karawang district in 2023. The method used is a quasi-experimental type with a non-equivalent control group design approach. The research results show that the Wilcoxon test results show the asymp value. Sig. (2-taileid) is